PERBAIKAN PRODUKTIVITAS PICKING ORDER DENGAN METODE ROUTING HEURISTIC DI GUDANG PUSAT SUKU CADANG OTOMOTIF - Mukhlisin Mukhlisin; Lien Herliani Kusumah (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Order picking is a process to fulfill customer order, with fast timing and provide high customer satisfaction. The order picking process is the highest cost in both manual and automatic systems, so it is necessary to improve efficiency and productivity. This study is aims to improve the productivity of order picking by shortening the distance. By choosing heuristic method using the application of interactive warehouse program, it is found that heuristic routing method can shorten picking distance. So, the routing heuristic method can increase the productivity of picking orders.